Evaluasi Pembelajaran Jarak Jauh: Tantangan dan Solusi Menuju Pendidikan Daring Berkelanjutan - Agus Trioni Nawa (CV. Creative Tugu Pena, 2024)
Distance Learning (PJJ) or online systems are now a popular educational model, requiring educational institutions to be more responsive and adaptive as a solution to ensure continuity of learning. Many studies state that online learning has a positive impact on learning outcomes, but have not focused on evaluating the challenges faced during the adaptation of the learning process. This study aims to evaluate the effectiveness of PJJ implementation, using a qualitative approach through summative evaluation methods. The research results show that the implementation of PJJ is still less than optimal due to the lack of an integrated Learning Management System (LMS) and low innovation in the delivery of material by educators, as well as the double burden of educators who also act as parents. This study recommends increasing teacher digital competence through training, providing an efficient LMS, and adapting an online learning-based curriculum to ensure the continuity of education that is responsive to the challenges of the current digital era